2007
DOI: 10.1073/pnas.0704632104
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a plant virus-encoded protein with the major nucleolar protein fibrillarin is required for systemic virus infection

Abstract: The nucleolus and specific nucleolar proteins are involved in the life cycles of some plant and animal viruses, but the functions of these proteins and of nucleolar trafficking in virus infections are largely unknown. The ORF3 protein of the plant virus, groundnut rosette virus (an umbravirus), has been shown to cycle through the nucleus, passing through Cajal bodies to the nucleolus and then exiting back into the cytoplasm. This journey is absolutely required for the formation of viral ribonucleoprotein parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
194
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(200 citation statements)
references
References 32 publications
3
194
0
3
Order By: Relevance
“…Although TEV NIa has been observed in the nucleolus (Schaad et al, 1996), detailed studies on nucleolar targeting of NIa have not been reported. Thus, our current findings on nucleolar and nuclear localization of a potyviral protein were made in a study area that has generally gained little attention in plant virology (Kim et al, 2007a(Kim et al, , 2007b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although TEV NIa has been observed in the nucleolus (Schaad et al, 1996), detailed studies on nucleolar targeting of NIa have not been reported. Thus, our current findings on nucleolar and nuclear localization of a potyviral protein were made in a study area that has generally gained little attention in plant virology (Kim et al, 2007a(Kim et al, , 2007b.…”
Section: Discussionmentioning
confidence: 99%
“…The ORF3 protein of GRV (Kim et al, 2007a) and some proteins of animal viruses interact with fibrillarin or certain other nucleolar proteins (reviewed in Hiscox, 2007), which prompted us to test whether PVA NIa could interact with fibrillarin. Two copies (Nb Fib2a and Nb Fib2b) …”
Section: Interaction Of Pva Vpg With the Nucleolar Protein Fibrillarinmentioning
confidence: 99%
See 2 more Smart Citations
“…In the best-studied system to date, the ORF3 long-distance movement protein of Groundnut rosette virus trafficks to the nucleolus via CBs, causing reorganization of CBs into multiple CBlike structures that fuse with the nucleolus. ORF3 then recruits fibrillarin (an abundant nucleolar RNA binding protein, known to be an RNA methylase) for assembly of cytoplasmic infectious viral particles (Kim et al, 2007a(Kim et al, , 2007bCanetta et al, 2008). The nucleolar localization of ORF3 is essential for systemic infection.…”
Section: The Nucleolus and Virus Infectionmentioning
confidence: 99%